2022
DOI: 10.1038/s41419-022-05116-w
|View full text |Cite
|
Sign up to set email alerts
|

Germline FOXJ2 overexpression causes male infertility via aberrant autophagy activation by LAMP2A upregulation

Abstract: Spermatogenesis is a complex biological process that produces haploid spermatozoa and requires precise regulation by many tissue-specific factors. In this study, we explored the role and mechanism of Fork head box J2 (FOXJ2, which is highly expressed in spermatocytes) in the regulation of spermatogenesis using a germline-specific conditional Foxj2 knock-in mouse model (Stra8-Cre; Foxj2tg/tg mouse). Foxj2 overexpression in mouse testes led to spermatogenesis failure, which started at the initiation of meiosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Enrichment analysis revealed that DMRs were involved in major male reproductive processes, including the development of testicular seminiferous tubules, spermatogonial differentiation, and meiosis. In addition, CIB2 , AK1 , FOXJ2 , PKDREJ , SLC9A3 , and TOPAZ1 genes in the hypermethylated DMRs were specifically expressed in spermatocytes and round sperm cells, regulating spermatogenesis [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In hypomethylated DMRs, it was found that BCL6 is associated with cell apoptosis [ 46 , 47 ], EPHA2 regulates self-renewal of SSCs [ 48 , 49 ], TAF12 regulates the transcription program of specific genes in the testes [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Enrichment analysis revealed that DMRs were involved in major male reproductive processes, including the development of testicular seminiferous tubules, spermatogonial differentiation, and meiosis. In addition, CIB2 , AK1 , FOXJ2 , PKDREJ , SLC9A3 , and TOPAZ1 genes in the hypermethylated DMRs were specifically expressed in spermatocytes and round sperm cells, regulating spermatogenesis [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In hypomethylated DMRs, it was found that BCL6 is associated with cell apoptosis [ 46 , 47 ], EPHA2 regulates self-renewal of SSCs [ 48 , 49 ], TAF12 regulates the transcription program of specific genes in the testes [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although increased levels of LAMP2A and HSC70 have been reported in the testes of the Stra8-cre;Foxj2 tg/tg sterile mice model 35 , the possible involvement of CMA in spermatogenesis has yet not been investigated in details. Analysis of the testes of KFERQ-PS-Dendra zebrafish showed low basal CMA activity in this tissue (Figures 3A1-3A3).…”
Section: A New and Key Role For Cma During Spermatogenesismentioning
confidence: 99%
“…Nowadays, many genes associated with cell death have been identified that may play a surprising role in the process of testicular spermatogenesis. In mouse testicular germ cells, Bai et al (2022) found that overexpression of FOXJ2 upregulates LAMP2A, which activates aberrant autophagy and leads to failure of spermatogenesis at the onset of meiosis, consequently contributing to MI. Gpx4, a crux upstream regulator of ferroptosis, attenuates its expression contributing to the restoring male fertility ( Ingold et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%